Isolation and Characterization of an Equine Adenovirus - Ardans, Alexander A. (1973)
A viral agent was isolated from lung tissue obtained upon necropsy of an Arabian foal which had exhibited clinical signs of pneumonia. The virus is 75 nm in diameter, cubic in symmetry, and resistant to chloroform and low pH (3.0). It contains deoxyribonucleic acid and has a buoyant density of 1.31 g/cm(3) in cesium chloride. These findings indicate that the virus is a member of the adenovirus group.